Koalisi Elite Politik dalam Pemekaran Daerah - Hilal Ramdhani (Universitas Medan Area, 2022)
This article aims to examine the political elite coalition in regional expansion. The problem is focused on the case of the expansion of the Cirebon Province since 2009, when the Presidium for the Establishment of the Cirebon Province (P3C) was declared. Until 2019, P3C has not been able to form a coalition of local political elites to propose the expansion of Cirebon Province. In order to approach this problem, the theoretical reference of the political elite coalition in regional expansion initiated by Ehito Kimura is used. The data collected through interviews and documentation, then analyzed qualitatively. This study concludes that the local political elite coalition did not form for the expansion of Cirebon Province due to differences in issues between local political elite groups who agree with local political elites who reject the issue of the use of economic resources, regional development, political interests, ethnicity and former political history. - Cirebon residency. In addition, the weakness of the local political elite coalition which is only supported by three regions and the corrupt behavior of the elites who approve the proposed expansion of Cirebon Province at both the lower and upper levels, resulted in the absence of the expansion of Cirebon Province during 2009-2019.